Political Participation and Gender : Political Marginalization of Women in Sarawak Politics - Nadrawina, Isnin (Universiti Malaysia Sarawak (UNIMAS), 2015)
This thesis is concerned with women’s political underrepresentation in Sarawak. This study aims to explore the reasons for women lacking at the decision making level of Sarawak’s political system. It also targets to examine the linkages between power structures and women roles in Sarawak’s political process; and to identify the ideological principles that encourages or discourages women from being involved. A mixed method is employed which is the prominence method for this research. Empirical evidence is conducted in Sarawak largely confirms the pervasiveness within society and within political parties which is male-dominated. The first major observation of this research maintains that the problem is due to the absence of political women attributed to various factors given that a patriarchal societal structure within the societies. Women in Sarawak were at the forefront for struggle of the sovereignty prior to independence in 1957. However, independence and statehood did not grant these female pugilists the same political status as their male counterparts. Second it was found that people have generally moved away from the negative stereotypes of women, but there is still a strong belief in male superior status. While the men assumed leadership roles, the women were systematically forced to remain in the grassroots or raised to the glorified status of the Women’s Wing of political parties. Even in this Wing, their political fate is sealed because aspirations to rise to higher levels are either sluggish or based on political connections which many are lacking. A third observation confirms that regardless of diversified cultures (Malay/Melanau, Iban and Chinese communities), divulged similar attitudes in relation to women in politics. Through interviews, all findings collected over a period of six months study suggests that, the women’s choices and loyalty does not guarantee a representation in the government or the decision-making level. The results indicate that patriarchal society and political patronage plays a vital role to realize political gains for the women if they wished to be in the upper level of the political echelon.